Financial Literacy and FinTech in Driving Firm Value: The Sequential Mediating Roles of Financial Risk Management and Financial Decision-Making - Agnes Ramey Rooroh; I Kadek Satria Arsana (Academic Bright Collaboration, 2026)
Purpose – Existing research on financial literacy and FinTech predominantly models their effects on firm value as direct or through parallel mediation, overlooking how these capabilities are translated through sequential organizational processes. This study addresses this limitation by examining a sequential mediation mechanism in which financial risk management precedes and shapes financial decision-making in linking financial literacy, FinTech adoption, and firm value among MSMEs. Methods – A cross-sectional survey conducted between September 2025 and January 2026 involving 462 MSME owners and financial decision-makers was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with sequential mediation, bootstrapping (5,000 resamples), and permutation-based Multi-Group Analysis (MGA) following MICOM procedures. Findings – All hypotheses were supported. While financial literacy and FinTech have significant direct effects on firm value, these effects are relatively modest. Stronger effects emerge through sequential pathways via financial risk management and financial decision-making, indicating that internal governance processes play a central role in value creation. No significant structural differences were found across regions. Research implications – The cross-sectional design limits causal inference, and perceptual measures of firm value may introduce bias. Further research using longitudinal data and objective performance indicators is needed. Originality – This study offers an empirically tested sequential mediation model that links financial literacy and FinTech to firm value through ordered governance mechanisms, extending dynamic capability theory with a process-based explanation of capability activation.